How to write effective business English the essential toolkit for composing powerful letters, e-mails and more, for today's business needs - Talbot, Fiona (Talbot, Fiona. Better business English., 2009)
How to Write Effective Business English teaches the non-native reader how to create clear, concise messages and avoid verbosity. Focusing on emails, letters, resumes or job applications, it gives readers an easy system for writing clearly, quickly and easily.